Business continuity management : a practical guide to organizational resilience and ISO 22301 - Crask, James (London Kogan page, 2021)
"Implement practical solutions in business continuity management and organizational resilience guided by international best practice from ISO 22301:2019. Business continuity management and organizational resilience are critical to maintaining a healthy business, but the process can easily become overly process-driven, too detailed and disengaging. As a consequence, many organizations either do nothing (leaving themselves exposed to disruption), take short cuts (leaving major gaps) or lose the interest of senior stakeholders. This book is a straightforward guide to implementing business continuity, including practical solutions built from the author's personal experience delivering hundreds of projects in a variety of business settings. Business Continuity Management explains how business continuity should sit within a wider risk and organizational resilience framework and how to explain its importance to senior decision makers to ensure appropriate investment. Readers will benefit from case studies of organizational crises and disruptions, a maturity model to plan and measure progress, Key Performance Indicators and templates and checklists covering planning, response, reporting and assurance. This book is the essential reference for business continuity and resilience, with frameworks and examples which can be tailored to any organization"--
Includes bibliographical references and index.
Keywords: Risk management; Risk management -- Standards; Organizational resilience; Crisis management